Role of Lipid Metabolism in Smoothened Derepression in Hedgehog Signaling. - Yavari, A.; Nagaraj, R.; Owusu-Ansah, E.; Folick, A.; Ngo, K.; Hillman, T.; Call, G.; Rohatgi, R.; Scott, M.P.; Banerjee, U. (Developmental Cell, 2010)
The binding of Hedgehog (Hh) to its receptor Patched causes derepression of Smoothened (Smo), resulting in the activation of the Hh pathway. Here, we show that Smo activation is dependent on the levels of the phospholipid phosphatidylinositol-4 phosphate (PI4P). Loss of STT4 kinase, which is required for the generation of PI4P, exhibits hh loss-of-function phenotypes, whereas loss of Sac1 phosphatase, which is required for the degradation of PI4P, results in hh gain-of-function phenotypes in multiple settings during Drosophila development. Furthermore, loss of Ptc function, which results in the activation of Hh pathway, also causes an increase in PI4P levels. Sac1 functions downstream of STT4 and Ptc in the regulation of Smo membrane localization and Hh pathway activation. Taken together, our results suggest a model in which Ptc directly or indirectly functions to suppress the accumulation of PI4P. Binding of Hh to Ptc derepresses the levels of PI4P, which, in turn, promotes Smo activation.